Lost in the Jungle - Hunt, Roderick, 2012; Roderick Hunt, 1986; Alex Brychta, 1986 (Oxford University Press, UK, 2012)
In Lost in the Jungle, the magic key whisks Biff, Chip, Kipper, Wilf, and Wilma away to a mysterious jungle. As they explore, they become separated and feel frightened by the unfamiliar sights and sounds. Strange noises, thick plants, and wild animals add to the suspense. The children must use their problem-solving skills and teamwork to navigate their way back. Just as the situation gets tense, the magic key activates again, safely returning them to their living room. They reflect on the adventure and how they managed to stick together and stay safe.
Series: Oxford Reading Tree (ORT) Stage: Stage 5 or 6 (depending on edition) Main Characters: Biff Chip Kipper Wilf and Wilma The Magic Key Setting: A dense, tropical jungle with wild animals and hidden dangers.
H3
ORT Stage 5 or 6 Suitable for readers gaining confidence with longer sentences, varied punctuation, and storytelling structure.
Keywords: Supplementary reading material